A cluster-optimized regulation method for distribution networks considering distributed photovoltaic heterogeneous characteristics - Junhao Li; Xin Wang; Qi Guo; Chunzhi Yang; Yizhe Chen; Ruifeng Zhao; Ming Li (International Journal of Electrical Power & Energy Systems, 2025)
With the increasing penetration of distributed photovoltaics (DPVs) in distribution networks (DNs), the problems of reverse power flow and voltage limit violation are becoming increasingly severe. Additionally, the data communication burden and computational complexity of DN regulation are amplified by the proliferation of DPVs with heterogeneous control modes (non-adjustable, limited-adjustable, and fully-adjustable). To address these challenges, a cluster-optimized regulation method is proposed, leveraging DPV heterogeneity to enable coordinated regulation while reducing directly-managed devices through DN clustering. First, a DN cluster division method considering improved voltage deviation sensitivity is developed to partition DNs into zones for targeted voltage violation mitigation. Second, the DPV model under different operation modes is constructed based on its heterogeneous characteristics. Further, a DN cluster-optimized model considering the DPV heterogeneous characteristics is constructed to achieve multi-objective optimization of the integrated DN operation cost and node voltage deviation. The cluster DN is then solved in a distributed-decoupled manner based on the synchronized alternating direction method of multipliers algorithm. Finally, the proposed cluster-optimized regulation method is validated and analyzed using a modified IEEE 69-node DN. Compared to the traditional DN regulation method without clustering, the DN operating cost of the proposed method is reduced by 25.03%, and the reverse power flow and voltage violation are completely solved.© 2017 Elsevier Inc. All rights reserved.